2021
DOI: 10.2903/j.efsa.2021.6893
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of a feed additive consisting of an aqueous extract of Citrus limon (L.) Osbeck (lemon extract) for use in all animal species (Nor‐Feed SAS)

Abstract: Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the safety and efficacy of an aqueous extract of Citrus limon (L.) Osbeck (lemon extract) when used as a sensory additive in feed for all animal species. The FEEDAP Panel concluded that the additive under assessment is safe for all animal species up to the maximum proposed use levels of 1,000 mg/kg complete feed and 250 mg/kg water for dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…The European Food Safety Authority (EFSA) Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) derived a no-observed-adverse-effect level (NOAEL) of 500 mg HSP/kg/day from the above - mentioned study. 14 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The European Food Safety Authority (EFSA) Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) derived a no-observed-adverse-effect level (NOAEL) of 500 mg HSP/kg/day from the above - mentioned study. 14 …”
Section: Introductionmentioning
confidence: 99%
“…The European Food Safety Authority (EFSA) Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) derived a no-observedadverse-effect level (NOAEL) of 500 mg HSP/kg/day from the above-mentioned study. 14 Matsumoto et al 10 recently reported OECD-compliant toxicity studies of GH showing that a subchronic oral (dietary admix) toxicity study in rats showed no deaths and no treatment-related adverse effects at 0.45%, 1.5%, and 5.0% GH, resulted in a NOEL of 5.0% GH in the diet, which corresponds to 3084 mg/kg/day for male rats and 3428 mg/kg/ day for female rats. Mayumi et al 15 performed a subchronic oral (dietary admix) toxicity study of methyl HSP in B6C3F mice and concluded that methyl HSP exerts no obvious toxic effects at a dose as high as 5.0%.…”
Section: Introductionmentioning
confidence: 99%
“…The safety of the additive Citrozest® when used at the maximum proposed use levels in feed for weaned piglets and growing poultry species has been already established in a previous opinion (EFSA FEEDAP Panel, 2021). The Panel concluded that the additive is safe for weaned piglets and all growing poultry up to 1,000 mg/kg complete feed.…”
Section: Assessmentmentioning
confidence: 99%
“…Hesperetin is a polyphenolic plant compound from the flavonoid group, derived from hesperidin and predominantly found in citrus fruits, such as oranges and grapefruit, whose intake is associated with a lower risk of neurodegenerative and cardiovascular diseases, along with neuroprotective effects in different models of neurodegenerative disorders [ 104 ]. The EFSA reported several studies that investigated the safety of hesperidin in rats, concluding that 500 mg/kg was the maximum dose showing no adverse effects, while the highest dose tested (1000 mg/kg/day) elicited significant alterations in body and organ weight, hematology, clinical chemistry and tissue histopathology [ 105 ].…”
Section: Impact Of Dietary Interventions On the Cognitive And Biochem...mentioning
confidence: 99%